RELATIONSHIP BETWEEN PICKY EATING AND NUTRITIONAL STATUS IN PRESCHOOL CHILDREN - Regitha Adit Pramesty; Esti Yunitasari; Dwiyanti Puspitasari (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground : Picky eating is a condition when children refuse to eat certain foods. Picky eating usually stops within 2 years as part of the growth process, those who stop picky eating after more than 2 years tend to be more difficult to accept new types of food. This may be unfavorable for a child's growth and nutritional status. The study was conducted to analyze the relationship between picky eating with nutritional status in preschool children. Method : This research method was observational analytic quantitative with cross sectional research design. Sampling used a total sampling technique. Data was collected in 3 preschool in October 2019 using primary and secondary data. Primary data was collected using a questionnaire given to parents to measure picky eating used Child Eating Behavior Questionnaire (CEBQ). Nutritional status was measured bytaking anthropometric measurements of children. Data analysis used fisher exact correlation tests. Results : The results obtained a sample of 78 respondents from 3 preschool. The average age of children was 48,37 months with a median was 49,00. The result showed 62,8% of children were female, 55,1% were second or more children, 88,5% had routine growth monitoring, 53,8% were in extended families, and 73,1% of children were taken care by their parents. The prevalence of children with picky eating was 70,5%. Nutritional status measurements found 1.3% of children included in underweight category and 83,3% normal. Results of the analysis of the relationship between picky eating and nutritional status showed p value = 0,819. Conclusion : There was no relationship between picky eating with nutritional status in preschool children.